Cash Waqf Link Sukuk untuk Pembangunan Berkelanjutan - Rizal Hendrawan (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2020)
ABSTRACTThe Indonesian government in its efforts to equalize economic inequality in the community has taken various methods, including meeting the basic needs of the community in terms of infrastructure, education and health as stipulated in the  RPJMN. However, the government faces a major obstacle, namely the lack of available budget to carry out the plan. Islamic finance has a very potential instrument to be used as an alternative source of financing in the form of Cash Waqf Link Sukuk. This instrument has a dual benefit impact, namely the principal funds are used by the State to develop Indonesia, while the monthly return is used for the benefit of the will by means of social assistance or building useful facilities. In this instrument there is also cooperation between the government and the community in the national development process.Keywords : Cash Waqf, Link Sukuk, and Infrastructure.